Integrasi Model Pendidikan Pondok Pesantren Salaf Dan Khalaf (Studi Kasus di Pondok Pesantren Irsyadul Anam Yogyakarta) - Abu Kholish; Moch. Khoirul Anam; Abrori (At Turots: Jurnal Pendidikan Islam, 2022)
This field research uses the approach of Islamic Education Science and Phenomenology in studying the integration of the education model of the salaf and khalaf Islamic boarding schools in the Irsyadul Anam Islamic Boarding School, Yogyakarta. This research uses descriptive qualitative data analysis. There are six background problems that make this research urgent to carry out. First, the current globalization requires that the Islamic boarding school education model not be implemented dichotomically. Second, the integration of the salaf and khalaf Islamic boarding school education models must be realized in order to answer the challenges of the times. Third, the integration pattern of the salaf and khalaf Islamic boarding school education models needs to be continuously studied and developed in order to find the ideal integration pattern. Fourth, we need a boarding school education model that integrates salaf and khalaf education. Fifth, the Irsyadul Anam Islamic Boarding School in Yogyakarta has implemented an integrated model of education for the salaf and khalaf Islamic boarding schools. Sixth, there is no similar research that examines the integration of the education model for the salaf and khalaf Islamic boarding schools in the Irsyadul Anam Islamic Boarding School, Yogyakarta. The results of this study indicate, first, the philosophical basis for the integration of the education model of the salaf and khalaf Islamic boarding schools in the Islamic Boarding School Irsyadul Anam Yogyakarta is the principle of "al-muhafadhotu 'ala al-qodimi al-sholih wa al-akhdzu bil jadidi al-ashlah" and the explanation of the letter. At-Taubah verse 122 and Surat al-Qoshos verse 77 which explain the importance of Islamic religious knowledge and general science as an integral unit. Second, the implementation of the integration of the salaf and khalaf Islamic boarding school education model at the Yogyakarta Irsyadul Anam Islamic Boarding School is carried out through the Islamic boarding school curriculum and the formal education curriculum through the MI Baburroyan and MTs Irsyadul Anam educational institutions in an integrated manner. Third, there are five opportunities and five challenges in implementing the integration of the salaf and khalaf Islamic boarding school education model at the Irsyadul Anam Islamic Boarding School, Yogyakarta.